(untitled) - Pinkaew Laungaramsri (Chennai, 2002)
This dissertation is an ethnography that offers a critical analysis of issues in contemporary conservation politics in Thailand. By examining the development of the dominant nature conservation ideology and response by the Karen, a group of ethnic hill people, to changing pattern of environmental control, the dissertation focuses on two main themes. The first part covers the Thai forest history and the role of development of scientific forestry in shaping discourses and practices of Thai nature conversation. The latter part explores Karen ecological knowledge and its chanllenge to the modern conservation paradigm
Keywords: Indigenous peoples,Nature conservation,Nature conservation,Người bản xứ,Bảo tồn thiên nhiên,Bảo tồn thiên nhiên; Ecology,Social aspects,Government policy,Sinh thái học,Khía cạnh xã hội,Chính sách của chính phủ; Thailand,Thailand,Thailand.,Thái Lan,Thái Lan,Thái Lan